A high-toughness flux-cored welding wire and its application

By using high-toughness flux-core welding wire in marine engineering structures, the alloy element content and welding process in weld metal are adjusted, and the impact toughness of weld metal is reduced after heat treatment is solved, and the high toughness of welding materials at low temperatures is achieved and stable mechanical properties.

CN115609186BActive Publication Date: 2024-12-27WUHAN TEMO WELDING CONSUMABLES CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211324052.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2024-12-27
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The impact toughness of the weld metal in marine engineering structures has significantly decreased after heat treatment and cannot meet the technical requirements.

Method used

High toughness flux core welding wire, including carbon steel outer skin and filler, is made of TiO2, feldspar, sodium fluoride, Si, Mn, Mg, Ni, B and other elements, and is protected and welded by CO2 gas and Heat treatment was performed at 620°C, and the alloy element content in the weld metal was adjusted to improve impact toughness.

Benefits of technology

It has excellent impact toughness in both welding and heat treatment states, with low-temperature impact absorption energy greater than 80J, tensile strength higher than 490MPa, elongation greater than 22%, and stable mechanical properties. It is suitable for marine engineering structure welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003911478360000071
    Figure BDA0003911478360000071
  • Figure BDA0003911478360000081
    Figure BDA0003911478360000081
  • Figure BDA0003911478360000082
    Figure BDA0003911478360000082
Patent Text Reader

Abstract

The present invention belongs to the technical field of welding materials, and specifically provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core comprises, by mass percentage, 30-38% TiO2, 5-8% feldspar, 3-5% smelting agent, 2-3% sodium fluoride, 2-5% Si, 13-17% Mn, 4-6% Mg, 2-4% Ni, 0.45-0.75% B, 0.02-0.04% C, and the balance is Fe. The high-toughness flux-cored welding wire provided by the present invention controls the contents of Ni, C, Mn, B and other alloy elements in the weld metal by adjusting the components of the flux sheath, so that the deposited metal has excellent impact toughness in both the welded state and the heat-treated state, and when CO2 gas shielded welding is adopted, the low-temperature impact absorption energy at -40°C is greater than 80J, the tensile strength is higher than 490MPa, the elongation is greater than 22%, and the mechanical properties are stable. Moreover, flux-cored welding wire can be used for all-position welding, with excellent welding process performance, stable arc and beautiful weld formation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding materials, and in particular relates to a high-toughness flux-cored welding wire and application thereof. Background Art

[0002] Marine engineering structures work under harsh environmental conditions and must withstand various climatic conditions and wind volume attacks. Therefore, the material selection must meet the special requirements of marine engineering. In order to reduce the mass of marine engineering structures and enhance the safety of the structures, the strength level of the steel used is getting higher and higher, and the thickness of the materials is also increasing. Due to the complexity of the marine engineering structure and the increase in its thickness, the stress concentration is high. Usually, the important parts and parts of the marine engineering structure need to be heat treated after welding to eliminate internal stress.

[0003] When carbon steel and low alloy steel are annealed between 550-650℃, it can be called low temperature annealing or stress relief annealing. During the stress relief annealing process, the changes in the structure may occur in the following aspects: on the one hand, the weld structure will generate a mixture of ferrite and cementite, namely pearlite, between 620-550℃, and quantitative studies have shown that for every 1% increase in pearlite volume, the ductile-brittle transition temperature increases by about 2℃. On the other hand, heat treatment will reduce the dislocation density in the structure, thereby reducing the strength of the weld metal; thirdly, heat treatment will cause carbides to precipitate at the grain boundaries, which may be detrimental to the impact properties.

[0004] However, as the thickness of the plate increases, the thickness of the weld also increases. During the welding process, the process of repeated heating of the previous weld by the latter weld will, on the one hand, cause the columnar crystals in the weld structure to grow, and at the same time, the chemical composition segregation, grain size and other aspects will deteriorate, thereby reducing the impact toughness value of the weld metal of the thick plate. In addition, when the plate thickness increases, the heat treatment time also needs to be extended. When high-temperature tempering is performed at 450℃-650℃, the extended holding time is likely to cause high-temperature tempering brittleness. The main reason is that as the holding time is extended, the metallographic structure will grow and coarsen, the precipitates will grow, and the composition will segregate, which will eventually lead to the deterioration of the mechanical properties of the weld metal. Therefore, these two reasons will cause the impact toughness of the weld metal of the thick plate welding to drop significantly after heat treatment, and cannot meet the technical requirements. To this end, the present invention provides a high-toughness flux-cored welding wire that can adapt to the production process of post-weld heat treatment of marine engineering structures, so that the weld still has good mechanical properties after heat treatment. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem in the prior art that the impact toughness of the weld metal of thick plate welding is significantly reduced after heat treatment and cannot meet the technical requirements.

[0006] To this end, the present invention provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core comprises, by mass percentage: 30-38% TiO2, 5-8% feldspar, 3-5% smelting agent, 2-3% sodium fluoride, 2-5% Si, 13-17% Mn, 4-6% Mg, 2-4% Ni, 0.45-0.75% B, 0.02-0.04% C, and the balance is Fe.

[0007] Specifically, the flux core accounts for 14.0-14.5% of the total mass of the flux-cored welding wire.

[0008] Specifically, the smelting agent is made from light rare earth oxides and magnesia by smelting fluoride at a high temperature of 1200°C.

[0009] The high-toughness flux-cored welding wire provided by the present invention can be used in marine engineering structure welding, and the welding conditions are: welding current 240-250A, welding voltage 28V, welding speed 28.0cm / min, and heat treatment is performed after welding.

[0010] Specifically, the high-toughness flux-cored welding wire adopts CO2 gas protection during welding.

[0011] Specifically, the heat treatment system is to keep the temperature at 620° C. for 4 hours.

[0012] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0013] The high-toughness flux-cored welding wire provided by the present invention controls the contents of Ni, C, Mn, B and other alloy elements in the weld metal by adjusting the coating components, so that the deposited metal has excellent impact toughness in both the welded state and the heat-treated state. When CO2 gas shielded welding is adopted,

[0014] -40℃ low temperature impact absorption energy is greater than 80J, tensile strength is higher than 490MPa, elongation is greater than 22%, and mechanical properties are stable. Moreover, flux-cored wire can be used for all-position welding, with excellent welding process performance, stable arc, and beautiful weld formation. DETAILED DESCRIPTION

[0015] The technical scheme in the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Although the representative embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and changes can be made to the present invention without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the embodiments, but should be limited by the attached claims and their equivalents.

[0016] The invention provides a high-toughness flux-cored welding wire, comprising a carbon steel outer skin and a flux core filled in the carbon steel outer skin, wherein the flux core comprises, by mass percentage, 30-38% TiO2, 5-8% feldspar, 3-5% smelting agent, 2-3% sodium fluoride, 2-5% Si, 13-17% Mn, 4-6% Mg, 2-4% Ni, 0.45-0.75% B, 0.02-0.04% C, and the balance is Fe. The flux core accounts for 14.0-14.5% of the total mass of the flux-cored welding wire; the smelting agent is made of light rare earth oxide and magnesia after being smelted at a high temperature of 1200°C by fluoride.

[0017] Among them, TiO2 can adjust the melting point and viscosity of slag, improve arc stability and weld formation. When the addition amount is less than 30%, the arc stability is poor, affecting the performance of vertical welding process; when the addition amount exceeds 38%, the weld formation will deteriorate, and the gas in the molten pool will not easily escape, resulting in pores. Therefore, the addition amount is controlled to 30-38%.

[0018] Sodium fluoride can be used as a dehydrogenating agent to reduce the diffusible hydrogen content of the weld. When the amount added is less than 2%, the dehydrogenating capacity is insufficient and the weld is prone to produce pores and pits; when the amount added exceeds 3%, welding spatter and smoke increase, affecting the welding process performance.

[0019] The light rare earth oxide in the flux can purify the weld, refine the inclusions and spheroidize the sulfide, thereby eliminating or reducing the harmful effects of trace low-melting-point metals in the metal material and improving the impact toughness. Magnesia can effectively improve the performance of vertical welding process. After smelting, the flux can control its particle size between 150-200 meshes and has good fluidity.

[0020] Si is the main deoxidizer. A certain amount of Si in the welding wire can reduce the oxygen content of the weld metal, improve low-temperature impact toughness, and adjust the fluidity of the molten iron. When the addition amount is less than 2%, it will lead to insufficient deoxidation, and the strength and low-temperature impact toughness of the weld metal cannot meet the requirements. When the addition amount exceeds 5%, it will affect the impact value of the post-weld heat treatment.

[0021] Mn is the main deoxidizer, which reduces the oxygen content of the weld metal and delays the transformation temperature of austenite, which helps to form a texture structure in the weld and improve low-temperature impact toughness. Mn also has a good effect on reducing the pearlite transformation rate, and increasing the Mn content also has a good effect on improving the impact toughness of post-weld heat treatment. When the Mn addition is less than 13%, it will lead to insufficient deoxidation and have no obvious effect on improving the low-temperature impact of post-weld heat treatment. When the addition exceeds 17%, the weld strength will be too high.

[0022] The appropriate amount of Mn and Si plays a role of combined deoxidation, avoiding defects such as pores in the weld and ensuring the quality of the weld.

[0023] Mg is a strong deoxidizer that improves impact toughness. When the added amount is less than 4%, the ability to improve low-temperature impact toughness and deoxidation is insufficient. When it is greater than 6%, the deoxidation product contains magnesium oxides, which increases the melting point of the slag and accelerates the solidification rate, which is not conducive to the removal of weld gas and will also cause the vertical welding to deteriorate.

[0024] Ni can reduce the low-temperature transformation temperature of the weld metal, which is beneficial to improving the low-temperature impact toughness.

[0025] C is a typical interstitial solid solution element that can improve the strength of weld metal. As the C content increases, the transformation rate of pearlite during heat treatment slows down, which will reduce the amount of pearlite and is beneficial to the low-temperature impact toughness after heat treatment.

[0026] Very low content of B element can greatly delay the formation of proeutectoid ferrite and pearlite in austenite. Therefore, B can not only improve low-temperature impact toughness, but also further reduce the pearlite content to ensure low-temperature impact after heat treatment. If the amount of B element added is less than 0.45%, the effect is not obvious. If the amount of B element added exceeds 0.75%, B compounds are easy to segregate, which is not conducive to low-temperature impact toughness.

[0027] The high-toughness flux-cored welding wire provided by the present invention adopts CO2 gas protection during welding, with a welding current of 240-250A, a welding voltage of 28V, a welding speed of 28.0cm / min, and a heat treatment system after welding of keeping warm at 620°C for 4 hours.

[0028] The high-toughness flux-cored welding wire of the present invention and the effects of its application are studied below through specific examples.

[0029] Embodiment 1:

[0030] This embodiment provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core components are shown in Table 1 in terms of mass percentage. The flux core accounts for 14% of the total mass of the flux-cored welding wire.

[0031] The high-toughness flux-cored welding wire provided in this embodiment was subjected to a test of the physical and chemical properties of the deposited metal. The groove, size, sampling method and position of the test plate were all carried out in accordance with the Chinese national standard GB / T 10045 "Non-alloy steel and fine-grained steel flux-cored welding wire". A DC reverse power supply was used for welding. CO2 gas protection was used during welding, the welding current was 240-250A, the welding voltage was 28V, the welding speed was 28.0cm / min, and the post-welding heat treatment system was kept at 620°C for 4 hours. The chemical composition of the deposited metal of the flux-cored welding wire is shown in Table 2, the mechanical properties of the deposited metal in the heat-treated state are shown in Table 3, and the mechanical properties of the deposited metal in the welded state are shown in Table 4.

[0032] Embodiment 2:

[0033] This embodiment provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core components are shown in Table 1 in terms of mass percentage. The flux core accounts for 14% of the total mass of the flux-cored welding wire.

[0034] The high-toughness flux-cored welding wire provided in this embodiment was subjected to a test of the physical and chemical properties of the deposited metal. The groove, size, sampling method and position of the test plate were all carried out in accordance with the Chinese national standard GB / T 10045 "Non-alloy steel and fine-grained steel flux-cored welding wire". A DC reverse power supply was used for welding. CO2 gas protection was used during welding, the welding current was 240-250A, the welding voltage was 28V, the welding speed was 28.0cm / min, and the post-welding heat treatment system was kept at 620°C for 4 hours. The chemical composition of the deposited metal of the flux-cored welding wire is shown in Table 2, the mechanical properties of the deposited metal in the heat-treated state are shown in Table 3, and the mechanical properties of the deposited metal in the welded state are shown in Table 4.

[0035] Embodiment 3:

[0036] This embodiment provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core components are shown in Table 1 in terms of mass percentage. The flux core accounts for 14% of the total mass of the flux-cored welding wire.

[0037] The high-toughness flux-cored welding wire provided in this embodiment was subjected to a test of the physical and chemical properties of the deposited metal. The groove, size, sampling method and position of the test plate were all carried out in accordance with the Chinese national standard GB / T 10045 "Non-alloy steel and fine-grained steel flux-cored welding wire". A DC reverse power supply was used for welding. CO2 gas protection was used during welding, the welding current was 240-250A, the welding voltage was 28V, the welding speed was 28.0cm / min, and the post-welding heat treatment system was kept at 620°C for 4 hours. The chemical composition of the deposited metal of the flux-cored welding wire is shown in Table 2, the mechanical properties of the deposited metal in the heat-treated state are shown in Table 3, and the mechanical properties of the deposited metal in the welded state are shown in Table 4.

[0038] Embodiment 4:

[0039] This embodiment provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core components are shown in Table 1 in terms of mass percentage. The flux core accounts for 14% of the total mass of the flux-cored welding wire.

[0040] The high-toughness flux-cored welding wire provided in this embodiment was subjected to a test of the physical and chemical properties of the deposited metal. The groove, size, sampling method and position of the test plate were all carried out in accordance with the Chinese national standard GB / T 10045 "Non-alloy steel and fine-grained steel flux-cored welding wire". A DC reverse power supply was used for welding. CO2 gas protection was used during welding, the welding current was 240-250A, the welding voltage was 28V, the welding speed was 28.0cm / min, and the post-welding heat treatment system was kept at 620°C for 4 hours. The chemical composition of the deposited metal of the flux-cored welding wire is shown in Table 2, the mechanical properties of the deposited metal in the heat-treated state are shown in Table 3, and the mechanical properties of the deposited metal in the welded state are shown in Table 4.

[0041] Embodiment 5:

[0042] This embodiment provides a high-toughness flux-cored welding wire, comprising a carbon steel sheath and a flux core filled in the carbon steel sheath, wherein the flux core components are shown in Table 1 in terms of mass percentage. The flux core accounts for 14% of the total mass of the flux-cored welding wire.

[0043] The high-toughness flux-cored welding wire provided in this embodiment was subjected to a test of the physical and chemical properties of the deposited metal. The groove, size, sampling method and position of the test plate were all carried out in accordance with the Chinese national standard GB / T 10045 "Non-alloy steel and fine-grained steel flux-cored welding wire". A DC reverse power supply was used for welding. CO2 gas protection was used during welding, the welding current was 240-250A, the welding voltage was 28V, the welding speed was 28.0cm / min, and the post-welding heat treatment system was kept at 620°C for 4 hours. The chemical composition of the deposited metal of the flux-cored welding wire is shown in Table 2, the mechanical properties of the deposited metal in the heat-treated state are shown in Table 3, and the mechanical properties of the deposited metal in the welded state are shown in Table 4.

[0044] Table 1 Composition of the flux core in the high-toughness flux-cored welding wire of each embodiment (%)

[0045] Example 1 Example 2 Example 3 Example 4 Example 5 TiO2 31 33 35 37 38 Feldspar 6 7 8 5 6 Sodium fluoride 2.2 2.5 2.8 2.8 3.0 Melting agent 5 4 3 3 3 Ferrosilicon 5 3 2 4 4 Manganese Metal 13 16 17 14 15 Magnesium powder 5 4.5 6 4 4.5 Nickel powder 4 2.5 2.2 3.5 3 graphite 0.02 0.04 0.04 0.03 0.03 Ferroboron 0.75 0.6 0.5 0.45 0.55 Fe margin margin margin margin margin

[0046] Table 2 Chemical composition of deposited metal in each embodiment (%)

[0047] C Si Mn P S Ni B Example 1 0.062 0.23 1.42 0.0086 0.0055 0.41 0.0057 Example 2 0.065 0.19 1.53 0.0087 0.0065 0.36 0.0051 Example 3 0.062 0.22 1.49 0.013 0.0046 0.44 0.0055 Example 4 0.066 0.25 1.56 0.015 0.0054 0.43 0.0056 Example 5 0.068 0.18 1.44 0.017 0.0081 0.43 0.0056

[0048] Table 3 Mechanical properties of deposited metal in each embodiment (heat treated state)

[0049]

[0050]

[0051] Table 4 Mechanical properties of deposited metal in various embodiments (welded state)

[0052]

[0053] As shown in Table 3 and Table 4, when the high-toughness flux-cored welding wire provided by the present invention adopts CO2 gas shielded welding, the deposited metal has excellent low-temperature impact toughness at -40°C in both the welded state and the heat-treated state, with an average value of up to 80J, a tensile strength greater than 490MPa, an elongation greater than 22%, and stable mechanical properties. It can adapt to the production process of post-weld heat treatment of marine engineering structures, so that the weld still has good mechanical properties after heat treatment, making the welding materials in the field of marine engineering more abundant.

[0054] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.

Claims

1. A high-toughness flux-cored welding wire, comprising a carbon steel outer skin and a flux core filled in the carbon steel outer skin, characterized in that: The core comprises, by mass percentage, 30-38% TiO2, 5-8% feldspar, 3-5% smelting agent, 2-3% sodium fluoride, 2-5% Si, 13-17% Mn, 4-6% Mg, 2-4% Ni, 0.45-0.75% B, 0.02-0.04% C, and the balance is Fe; the smelting agent is made of light rare earth oxide and magnesia after smelting fluoride at a high temperature of 1200°C.

2. The high-toughness flux-cored welding wire according to claim 1, characterized in that: The flux core accounts for 14.0-14.5% of the total mass of the flux cored welding wire.

3. Application of the high-toughness flux-cored welding wire as described in any one of claims 1-2 in welding of marine engineering structures.

4. The use of the high-toughness flux-cored welding wire as claimed in claim 3 in marine engineering structure welding, characterized in that: The welding conditions of the high-toughness flux-cored welding wire are: welding current 240-250A, welding voltage 28V, welding speed 28.0cm / min, and heat treatment after welding.

5. The application of the high-toughness flux-cored welding wire as claimed in claim 4 in marine engineering structure welding, characterized in that: The high-toughness flux-cored welding wire adopts CO2 gas protection during welding.

6. The application of the high-toughness flux-cored welding wire as claimed in claim 4 in marine engineering structure welding, characterized in that: The heat treatment system is to keep the temperature at 620° C. for 4 hours.

Citation Information

Patent Citations

  • Gas-shielded flux-cored wire for maritime engineering

    CN103692110A

  • 460MPa-level flux-cored wire for ocean engineering and application thereof

    CN105269174A

  • Flux-cored wire for gas shield arc welding

    JP2017170518A